2021
DOI: 10.1007/s10047-021-01274-4
|View full text |Cite
|
Sign up to set email alerts
|

Hemoadsorption with CytoSorb® and the early course of linezolid plasma concentration during septic shock

Abstract: Hemoadsorption with CytoSorb® becomes increasingly established in treatment of various, predominantly inflammation-associated diseases. In septic shock, results suggest improvements in hemodynamics and organ function. However, little is known about the in vivo adsorption properties for various antibiotics. We present the case of a 61-year-old female patient with known Ulrich Turner syndrome who treated supportively with CytoSorb® and with linezolid due to a Staphylococcus epidermidis bloodstream infection as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Third, the device may adsorb various drugs, such as some antibiotics, antimycotics or antivirals. [49][50][51][52][53] An in vitro study suggested the need for administration of an additional antibiotic dose within the first few hours of CytoSorb ® treatment and for early therapeutic drug monitoring since all antimicrobial drugs tested were adsorbed by the cartridge in relevant amounts. 49 However, reliable quantitative clinical data is needed to confirm these findings.…”
Section: Relationship To Previous Studiesmentioning
confidence: 99%
“…Third, the device may adsorb various drugs, such as some antibiotics, antimycotics or antivirals. [49][50][51][52][53] An in vitro study suggested the need for administration of an additional antibiotic dose within the first few hours of CytoSorb ® treatment and for early therapeutic drug monitoring since all antimicrobial drugs tested were adsorbed by the cartridge in relevant amounts. 49 However, reliable quantitative clinical data is needed to confirm these findings.…”
Section: Relationship To Previous Studiesmentioning
confidence: 99%
“…Khöler et al measured the blood levels of linezolid given as a 60 min infusion at different time points (before, 15, 60, 120 and 480 min) in a postoperative patient treated with Cytosorb ® and demonstrated that the blood levels after 8 h were below the therapeutic range [ 27 ].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…An additional dose has been recommended for fluconazole and linezolid only [ 160 ]. First clinical data for linezolid suggest similar behavior in humans [ 159 ]. Due to the initial high volume of distribution and the decrease in clearance within a few hours after CytoSorb ® installation, various authors recommend an additional anti-infective dose per adsorber for a variety of antibiotics [ 127 , 141 , 159 , 170 ].…”
Section: Hemoadsorption With Cytosorb ®mentioning
confidence: 99%
“…First clinical data for linezolid suggest similar behavior in humans [ 159 ]. Due to the initial high volume of distribution and the decrease in clearance within a few hours after CytoSorb ® installation, various authors recommend an additional anti-infective dose per adsorber for a variety of antibiotics [ 127 , 141 , 159 , 170 ]. Drug monitoring under hemoadsorption therefore seems to be essential [ 160 ].…”
Section: Hemoadsorption With Cytosorb ®mentioning
confidence: 99%